Are There Returns to the Wages of Young Men from Working While in School? - Hotz, V. Joseph; Xu, Lixin Colin; Tienda, Marta; Ahituv, Avner (The Review of Economics and Statistics, 2002)
This paper examines the effects of work experience acquired while youth were in high school (and college) on young men's wage rates. Previous studies have found sizeable and persistent rates of return to working while enrolled in school, especially high school, on subsequent wage growth. We evaluate the extent to which these estimates represent causal effects by assessing the robustness of prior findings to controls for unobserved heterogeneity and sample selectivity. We explore more-general econometric methods for dealing with the dynamic of selection and apply them to data on young men from the 1979 National Longitudinal Survey of Youth (NLSY79). We find that the estimated returns to working while in high school or college are dramatically diminished in magnitude and are not statistically significant when one applies dynamic selection methods.